Research Needs of Tropical Rain Forests of India. - Bahuguna, V. K. (Indian Forester, 1986)
Tropical rain forests in India are climatic climax of a region covering fairly extensive areas in the Western Ghats, North-eastern India and Andaman and Nicobar islands These forests, dynamic but fragile, are fast disappearing on account of biotic interferences and poor management. This paper deals with the probable research areas, to develop a sound scientific managemeni base for these Forests. Research should be carried out in such a manner that ecology, silviculture and management, are blended judiciously in dealing with rain forest. Studies on the structure and distribution of these forests in different geological, climatic and geographical zones typological studies for earmarking clearly types and sub-types, auto-ecological and syn-ecological, quantitative ecological and ecosystem modelling are discussed. The either research areas, identified, are in the field of genetics, silviculture, wood sciences. Logging, Wildlife, Pests and diseases, watershed management, develorment of trihologically viable socio-economic packages intergrating various fields of developmental activities, for setting the tribals, practising shifting cultivation.